2018
DOI: 10.3390/cli6030058
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling of Future Temperature and Precipitation Extremes in Addis Ababa under Climate Change

Abstract: One of the recent advances in climate science research is the development of global general circulation models (GCMs) to simulate changes in climatic elements of the present and future, which helps us to determine consequences earlier and prepare for necessary adaptation measures. However, it is difficult to apply the raw data of GCMs at a local scale, such as the urban scale, without downscaling due to coarse resolution. This study, therefore, statistically downscaled daily maximum temperature, minimum temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The past record on flooding in Addis Ababa indicates, it was increasing from time to time. There are a wide evidence that the flooding in Addis will be continue to increase to the end of this century due to climate change (CLUVA 2011;Ward and Lasage 2009;McSweeney et al 2010;Feyissa et al 2018) and poor urban storm water management in Addis Ababa. The exposure layer of climate change vulnerability identified in these analyses indicates the flood is common in poor infrastructure areas, low quality housed but dense population along streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past record on flooding in Addis Ababa indicates, it was increasing from time to time. There are a wide evidence that the flooding in Addis will be continue to increase to the end of this century due to climate change (CLUVA 2011;Ward and Lasage 2009;McSweeney et al 2010;Feyissa et al 2018) and poor urban storm water management in Addis Ababa. The exposure layer of climate change vulnerability identified in these analyses indicates the flood is common in poor infrastructure areas, low quality housed but dense population along streams.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reveal that climate change and variability severely affect economic conditions livelihoods and agricultural production and food security, water resources and health (Gebregiziabhre et al 2016, Legese et al 2016, Tafesse et al 2016, Melese 2016, Abebe and Kebede 2017, Amare and Simane 2017. The impact of climate change in urban scale is also studied in towns like Dire Dawa (Billi et al 2015), Addis Ababa (CLUVA 2011;Cochrane and Costolanski 2013;Birhanu et al 2016;Feyissa et al 2018) indicating the identified cities are vulnerable to climate change impacts mainly flooding and urban heat.…”
Section: Introductionmentioning
confidence: 99%
“…Using various General Circulation Model, Feyissa et al. suggested future climatic changes and argued that rise in temperature will exacerbate the urban heat highland effects in warm seasons and an increase in precipitation (Feyissa et al 2018). Some environmental harms such as high temperature and extreme rainfall, which results in flooding in Addis Ababa, could be signals of climate change (Birhanu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Coefficient of determination (R 2 ) is higher in downscaled temperature than IPCC. Using CGCM3A2 and RCP 4.5 the maximum temperatures increases from 0.03°C-0.21°C in 2020 [41].…”
Section: Monthly and Yearly Variability Of Temperaturementioning
confidence: 99%